2017
DOI: 10.1016/j.fertnstert.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of anastrozole in oligozoospermic hypoandrogenic subfertile men

Abstract: Approximately 95% of men with hypoandrogenism responded with improved endocrine parameters, and a subset of oligozoospermic men (approximately 25% of all patients) displayed significantly improved sperm parameters. In that subset, increase in sperm parameters was correlated with the change in the T/E ratio, which argues for a physiologic effect of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 30 publications
1
62
1
Order By: Relevance
“…A recent study showed that 20% of infertile men are hypogonadal (Ventimiglia et al, ). Others have shown 40%–45% of men with abnormal semen parameters are hypogonadal (Shoshany, Abhyankar, Mufarreh, Daniel, & Niederberger, ; Sussman, Chudnovsky, & Niederberger, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that 20% of infertile men are hypogonadal (Ventimiglia et al, ). Others have shown 40%–45% of men with abnormal semen parameters are hypogonadal (Shoshany, Abhyankar, Mufarreh, Daniel, & Niederberger, ; Sussman, Chudnovsky, & Niederberger, ).…”
Section: Introductionmentioning
confidence: 99%
“…<10) might benefit from aromatase inhibitors as a treatment of infertility. Anastrozole (1 mg once daily) and letrozole (2.5 mg once daily) are used for treatment of impaired spermatogenesis, although this represents an off-label use [51] , [52] . They can increase endogenous testosterone production and serum testosterone levels.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of human chorionic gonadotropin, clomiphene citrate, and aromatase inhibitors have been limited by their small sizes and short durations, and randomized controlled trials are lacking to establish their efficacy and safety (43,44). In one trial of 85 men treated with clomiphene citrate, adverse events among four participants included depression, erythrocytosis, ischemic stroke, and psoriatic arthropathy (43).…”
Section: Risks Of Testosterone and Supplementsmentioning
confidence: 99%
“…In case reports, use of clomiphene citrate has been associated with acute mania, central retinal vein occlusion, pulmonary embolism, and suicidal behavior (45)(46)(47)(48). Aromatase inhibitors decrease bone density and have been associated with breast tenderness, depression, joint pain, limb swelling, and tendon pain (44).…”
Section: Risks Of Testosterone and Supplementsmentioning
confidence: 99%